Orthogonal Time/Frequency Multiplexed Modulation Families for Software Defined Radio - Lin, Wei-Lun (Recent Advances in Communications and Networking Technology, 2016)
The uplink and downlink transmissions in Long-Term Evolution (LTE) systems are performed using single-carrier and multicarrier modulation schemes, respectively. To respond such trend, orthogonal time-multiplexed modulation (OTMM) is proposed as several new single-carrier modulation families originated from the orthogonal multiplexed modulation (OMM) families to provide low peak-to-average power ratio and versatile modulations with different degrees in power and bandwidth efficiencies. To further facilitate a software defined radio (SDR) implementation, the proposed OTMM families are incorporated into the original OMM family in a unified signal structure. Typical basis sets are also unified to suit an SDR implementation. To establish a unified modulation platform, the present study therefore proposes a set of orthogonal time-multiplexed modulation (OTMM) families to complement the existing set of orthogonal multiplexed modulation (OMM) schemes. The OTMM and OMM families are integrated in a software defined radio (SDR) modulation structure by means of a common signal model and five unified basis sets. The resulting structure supports both time multiplexing and frequency multiplexing, and therefore offers greater flexibility in improving the power and bandwidth efficiencies of the LTE system. The proposed structure thus attends throughput and signal robustness simultaneously in hostile environments and also provides versatile choices in modulations with low peak-to-average power ratio.
Keywords: LTE system